Impact of estrogen receptor expression on prognosis of ovarian cancer according to antibody clone used for immunohistochemistry: a meta-analysis - Chun Wai Ng; Kwong-Kwok Wong (BMC, 2022)
Abstract Background The prognostic value of the expression of estrogen receptor (ER) subtypes ER⍺ and ERβ in ovarian cancer has previously been evaluated by meta-analyses. However, the results are contradictory and controversial. Methods We conducted an updated meta-analysis with stringent inclusion criteria to ensure homogeneous studies to determine the effect of ER subtypes on ovarian cancer prognosis. Articles were retrieved by systematic search of PubMed and Web of Science for articles dated up to June 2021. Only studies with known hazard ratio (HR) and antibody clone for immunochemistry (IHC) were included. Pooled HRs with the corresponding 95% confidence intervals (CIs) were calculated for the effect of ER⍺ and ERβ expression on ovarian cancer patient progression-free survival (PFS) and overall survival (OS). Results A total of 17 studies were included, of which 11 and 13 studies examined the relationships between ER⍺ expression and PFS and OS, respectively, and 5 and 7 studies examined the relationships between ERβ expression and PFS and OS, respectively. Neither ER⍺ expression (random-effects model; HR = 0.99, 95% CI = 0.83-1.18) nor ERβ expression (fixed-effects model; HR = 0.94, 95% CI = 0.69-1.27) was associated with PFS. Random-effects models showed that ER⍺ expression (HR = 0.81, 95% CI = 0.64-1.02) and ERβ expression (HR = 0.75, 95% CI = 0.50-1.13) were only marginally and not significantly associated with better OS. Subgroup analysis revealed that ER⍺ expression determined using antibody clone 1D5 (HR = 0.75, 95% CI = 0.64-0.88) and ERβ expression determined using ERβ1-specific-antibody clone PPG5/10 or EMR02 (HR = 0.65, 95% CI = 0.50-0.86) were associated with significantly better OS, but ER expression determined using other antibodies was not. Conclusions In conclusion, a higher ER⍺ expression and ERβ expression are significantly associated with a better survival of ovarian cancer patients, but the results from previous prognostic studies are significantly dependent on the choice of specific ER antibody clones used in immunohistochemistry analysis.